Ecologies of Faith in New York City : The Evolution of Religious Institutions - Huang, Weishan, 1969-; Mian, Nadia A., 1979-; Cimino, Richard P. (Book collections on Project MUSE., 2013)
Ecologies of Faith in New York City examines patterns of interreligious cooperation and conflict in New York City. It explores how representative congregations in this religiously diverse city interact with their surroundings by competing for members, seeking out niches, or cooperating via coalitions and neighborhood organizations. Based on in-depth research in New York's ethnically mixed and rapidly changing neighborhoods, the essays in the volume describe how religious institutions shape and are shaped by their environments, what new roles they have assumed, and how they relate to other r.